By way of deception : A devastating insider's portrait of the Mossad - Hoy, Claire; Ostrovsky, Victor (U.S.A. : Stoddart publishing, 1990)
Allegations about the Mossad and the Beirut Marine bombing, American hostages in Lebanon, Iran-Contra, Andrew Young, etc.
Includes index.
Keywords: Intelligence officers -- Israel; Secret service -- Israel